The Role of Local Government in Implementing the Planting for Food and Jobs Programme: A Case Study of Nsawam‒Adoagyiri Municipal Assembly - Aziba, I.M. (University of Ghana, 2021)
he objective of every agriculture policy is to improve agriculture production and food systems. Meanwhile, in the Local Government Act of 1993 (Act 462), agriculture services at the local level are ceded to the local government and the Departments of Agriculture became unit within the Metropolitan, Municipal, and District Assemblies (MMDAs). Given the importance of agriculture growth at the local level, this study investigates the role local government plays in implementing the Planting for Food and Jobs programme (PFJ) in the Nsawam Municipality. The study used a mixed method research approach to collect primary data by administering questionnaires to 100 selected farmers, scheduled interviews with 8 Local Government Officials, and 4 Focus Group Discussions with farmers. The SPSS software was used to analyze the quantitative data and the thematic analysis technique was used for the qualitative data. The results revealed that the local government played a significant role in implementing the Planting for Food and Jobs programme in the Nsawam Municipality. Most respondents expressed satisfaction with the way the programme is being implemented and indicated the programme has increased their yields, improved access to extension services, fertilizers, and seeds. However, late delivery of the agriculture inputs, lack of logistics and equipment, lack of an organized system to regulate farmer's noncompliance, and inadequate staff, especially Field Officers were challenges that affected the roles local government played in implementing the programme. In line with the findings, the study recommends that the Departments of Agriculture within the MMDAs should be adequately resourced in terms of financial, human, and working logistics to undertake their functions. This will strengthen the role of local government in implementing the PFJ programme in the Nsawam Municipality, and across the 260 MMDAs in Ghana as a whole.
MA. Development Studies
Keywords: agriculture policy; agriculture production; food systems